Clinical Nursing and Midwifery Research Priorities in Eastern and Southern African Countries: Results From a Delphi Survey. Issue 6 (November 2015) - Sun, Carolyn; Dohrn, Jennifer; Klopper, Hester; Malata, Address; Omoni, Grace; Larson, Elaine
Abstract : Background: Because of the profound shortage of nurse and midwifery researchers in many African countries, identification of clinical nursing and midwifery research is of highest priority for the region to improve health outcomes. Objectives: The aim of this study was to gain consensus from experts on the priorities of clinical nursing and midwifery research in southern and eastern African countries. Method: A Delphi survey was conducted among experts in the region. Criteria for "expert" included (a) a professional nurse, (b) a bachelor's degree or higher in nursing, (c) published research, (d) affiliated with a school of nursing with at least a master's level nursing program, and/or (e) identified by the African core collaborators as an expert in the region. A list of candidates was identified through searches of published and gray literature and then vetted by core collaborators in Kenya, Malawi, and South Africa. Core collaborators held leadership roles in a nursing school and a doctoral degree in nursing, had conducted and published nursing research, and resided in an included country. Results: Two rounds of the Delphi survey were required to reach consensus. In total, 40 participants completed both rounds, and at least one participant from each country completed both rounds; 73% and 85% response rates were achieved for each round, respectively. Critical clinical research priorities were infectious disease/infection control and midwifery/maternal health topics. These included subtopics such as HIV/AIDS, tuberculosis, maternal health and mortality, infant mortality, and obstetrical emergencies. Many other topics were ranked as important including patient outcomes, noncommunicable diseases, and rural health. Discussion: Areas identified as research priorities were consistent with gaps identified in current literature. As evidenced by previous research, there is a lack of clinical nursing and midwifery research in these areas as well as nurses and midwives trained to conduct research; these priorities will help direct resources to the most essential research needs.